1970
DOI: 10.1002/1097-0142(197002)25:2<253::aid-cncr2820250204>3.0.co;2-u
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity of E. coli L-asparaginase in man

Abstract: During therapeutic trials with E. coli L‐asparaginase in 131 children and 143 adults with neoplastic disease the following signs of toxicity have been observed: fever, nausea and vomiting, weight loss, somnolence, lethargy, confusion, hypolipidemia, hyperlipidemia, hypoproteinemia, abnormal liver function tests, fatty metamorphosis of the liver, pancreatitis (in rare instances), azotemia, granulocytopenia, lymphopenia, thrombocytopenia, and hypersensitivity reactions. While these effects have been moderately s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
80
1
5

Year Published

1970
1970
2004
2004

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 246 publications
(87 citation statements)
references
References 47 publications
1
80
1
5
Order By: Relevance
“…4 A number of different dosages and schedules have been employed, but whether the incidence of allergic reactions is dose-or schedule-dependent is controversial. Oettgen et al 12 reported that the risk of Relationship between anti-asparaginase antibody levels measured at the end of reinduction (after a median of 25 doses and allergic reactions) and elapsed time between the last reaction and sample collection for post-reinduction antibody levels.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…4 A number of different dosages and schedules have been employed, but whether the incidence of allergic reactions is dose-or schedule-dependent is controversial. Oettgen et al 12 reported that the risk of Relationship between anti-asparaginase antibody levels measured at the end of reinduction (after a median of 25 doses and allergic reactions) and elapsed time between the last reaction and sample collection for post-reinduction antibody levels.…”
Section: Figurementioning
confidence: 99%
“…9 It has been suggested that development of antibodies may hamper the antileukemic effect of asparaginase by shortening its half-life, preventing or delaying absorption after intramuscular injection, or interfering with enzyme activity. 3,10,11 The reported frequency of anti-asparaginase antibodies is quite variable, and so high in some subgroups of patients (ie over 70% in adults receiving E. coli asparaginase) 10,12 that it is not clear whether antibody levels are more frequently detected or higher in patients who exhibit overt clinical allergy than in identically treated patients without clinical evidence of hypersensitivity. Therefore, the objective of this study was to retrospectively compare anti-asparaginase antibody concentrations at identical time points relative to therapy in ALL patients who did and who did not develop hypersensitivity reactions to asparaginase.…”
Section: Introductionmentioning
confidence: 99%
“…7,[14][15][16][17][18][19][20] The reported frequency of antiasparaginase antibodies was as high as 78% in adults and 70% in children following intravenous or intramuscular administration of E. coli asparaginase. 21 In all, 23-30% of children developed allergic reaction while receiving Erwinia asparaginase. 14,17 Allergic reaction was observed in 30-41% of patients who received PEG asparaginase.…”
Section: Introductionmentioning
confidence: 99%
“…18,22 Recently, the importance of 'silent hypersensitivity' has been recognized in patients who developed antiasparaginase antibodies without clinical evidence of a hypersensitivity reaction. 6,9,12,21 Investigators found that those patients had a significant reduction in plasma asparaginase activity 9 and suboptimal asparagine depletion. 23 Allergic reactions to one preparation can be circumvented in most patients by the substitution to another preparation.…”
Section: Introductionmentioning
confidence: 99%
“…Anti-asparaginase antibodies occur in as many as 70% of children receiving E. coli asparaginase. 3,[10][11][12] The best course of action, including the use of premedications and substitution with PEG, or Erwinia asparaginase, in cases with frank or silent hypersensitivity to E. coli asparaginase, is also not clear.…”
Section: Introductionmentioning
confidence: 99%